Self-paced computer-based training module for Training Learning Management System (LMS): instructional design consideration based on Gagné’s Nine events of instruction - Abdul Talib, Mohd. Fairuz (2014)
Training is essential in ensuring smooth implementation of Learning Management Systems (LMS’s). However, traditional face-to-face training has been associated with limitations such as time-consuming, and resource intensive. Therefore, computer-based training module is seen as viable solution. In designing and developing such a module, it must be based on instructional design principles. This paper describes the design and development of a self-paced computer-based training module for training learning management system based on the application of Gagné’s Events of Instruction. The module will be used as an alternative to traditional face-to-face training session. The study seeks to see whether all events can be or need to be implemented, and whether they have to be implemented in the proposed sequence as viewed by Gagné as the approximate order in which they were typically employed. Based on the researcher’s experience during the design and development of the initial prototype, it was found that not all nine events in Gagné’s model need to be spelled out explicitly, due to the fact that they might occur as a result of other factors. Furthermore it is also found that these events can be presented out of sequence.